2020
DOI: 10.1002/essoar.10503320.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seismic discrimination of controlled explosions and earthquakes near Mount St. Helens using P/S ratios

Abstract: Explosions and earthquakes are effectively discriminated by P/S amplitude ratios for moderate magnitude events (M[?]4) observed at regional to teleseismic distances ([?]200 km). It is less clear if P/S ratios are effective explosion discriminants for lower magnitudes observed at shorter distances. We report new tests of P/S discrimination using a dense seismic array in a continental volcanic arc setting near Mount St. Helens, with 23 single-fired borehole explosions (ML 0.9-2.3) and 406 earthquakes (ML 1-3.3).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Encouraging performance without local correction factors does not imply that such corrections are unimportant. In regions where sufficient data exist to calibrate local corrections, we expect that incremental but important improvements in performance are possible for a given number of stations (e.g., Kintner et al., 2020; Wang et al., 2020). Lastly, both methods used here are fast to calculate, making the joint method practical for near‐real time screening at local scale (e.g., Dempsey et al., 2020; Scafidi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging performance without local correction factors does not imply that such corrections are unimportant. In regions where sufficient data exist to calibrate local corrections, we expect that incremental but important improvements in performance are possible for a given number of stations (e.g., Kintner et al., 2020; Wang et al., 2020). Lastly, both methods used here are fast to calculate, making the joint method practical for near‐real time screening at local scale (e.g., Dempsey et al., 2020; Scafidi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All broadband three‐component records are filtered between 10 and 18 Hz, which is the optimal band for discrimination of similar‐magnitude sources at comparable distances in Wang et al. (2020). Modified after O’Rourke et al.…”
Section: Methodsmentioning
confidence: 99%
“…With growing time‐histories of data and associated event catalogs, recent work using data from regional networks in Utah and the Netherlands has demonstrated that machine learning can play an increasingly important role in this problem (Linville et al., 2019; Trani et al., 2021). At local scales, data from the Mount Saint Helens nodal array and from a dense network in Wyoming have been used to explore the use of classical P / S amplitude ratios for explosion discrimination (O’Rourke et al., 2016; R. Wang et al., 2020). Using the dense data deployments, both studies identified strong site effects that varied over relatively short distances.…”
Section: Science Enabled By Big Data Seismologymentioning
confidence: 99%
“…In addition, explosion signals show a shorter rise time and duration as well as a higher frequency content compared to earthquakes. Unlike tectonic earthquakes, both nuclear and chemical explosions are dominated by P waves and radiate weaker S waves over all frequencies, especially for frequencies greater than 10 Hz (Wüster 1993 ; Kim et al 1994 ; Prastowo and Madlazim 2018 ; Wang et al 2020 ). The P wave is then followed by high amplitude Rayleigh waves, which are strongly affected by the explosions’ depth and the overlying topography (Stevens et al 2017 ).…”
Section: Seismic Sourcesmentioning
confidence: 99%